Urban Consolidation in Australia's Four Largest Capital Cities: Tangible Outcomes of Inner-city Apartment Developments and Their Implications for Urban Planners - Lees, Christina (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
Urban consolidation has become dominant practice in metropolitan planning across Australia’s four largest capital cities – Sydney, Melbourne, Brisbane and Perth – as a result of the escalating need to manage rapid population growth and limit urban expansion. The strategic push for higher-density residential dwellings, such as apartment complexes, around strategic infill locations and activity centres is partly in response to the rising demand for more diversity in Australia’s housing stock. Supplementary factors include demographic shifts, cultural changes, and ongoing concerns regarding housing affordability, liveability, accessibility and climate change. Although this style of development has been at the forefront of state government planning agendas for at least a decade, presently little is understood about the outcomes of inner-city apartment buildings, particularly in Perth, as most of the research on modern infill projects in Australia focuses on Sydney and Melbourne.The primary aim of this research is, therefore, to investigate the outcomes of high- Density inner-city apartment developments for residents, the community and urban planners within Australia’s four largest capital cities, with a particular focus on Perth. The research is informed by a review of academic and government literature concerning infill and apartment developments in the specified cities, as well as a case study of a recently constructed apartment building in one of Perth’s main activity centres, Fremantle. The study found that state and local governments are not always achieving ‘good density’, nor are they developing apartment buildings that engender positive outcomes for both residents and the community. Some of the challenges that must be overcome if this is to change include designing apartments that cater to the needs of a diverse population, getting state governments to provide more support for local councils, and engaging earlier and more effectively with local communities. The research findings provide council planners with a better understanding of the challenges faced by residents in new apartment buildings, as well as the difficulties of meeting community expectations and planning ‘good density’, so that future planning policies and urban development can be more suitably informed.